The knowledge economy and the economic crisis in Germany. Regional development, structural change and labor market regions - Michael Bentlage; Matthias Dorner; Alain Thierstein (European Regional Science Association (ERSA), 2015)
Regions in Germany are facing an intensifying structural change towards the knowledge economy which is affecting spatial patterns of growth. . Features of such a change know many facets: fierce competition for skilled, mobile and motivated labor force, unemployment of non-qualified labor, longer commutes, multi-local households, re-concentration of the value chain, increased knowledge intensity of innovations, triple-helix collaborative ventures, structural weakness of public budgets, etcetera. These changes result in uneven spatial development, concentration in polycentric large-scale urban regions and increase in spatial disparities. The question arises how this structural change affects the territory of Germany, where securing equivalent living conditions still counts among the basic constitutional principles. We hypothesize that knowledge intensive employment tends to concentrate in two different spatial environments: (1) urban metropolitan centers and (2) network nodes with specialized knowledge resources. Both spatial configurations qualify by their combination of agglomeration economies and network economies. And both spatial environments tend to provide an optimum of geographical proximity and relational proximity, which eventually enable systematic knowledge creation. We test our hypothesis by analyzing the employment from 1998 to 2010 in 16 branches of the knowledge economy with a shift-share analysis. We argue that structural change and the economic crisis from 2009 intensify regional disparities while inducing relative employment shifts.
Keywords: R11; R12; O1; 330; employment growth; economic crisis; knowledge economy; labor market regions